Development of 3D Animated Video Application for Computer Evolution - Ali, Azita; Pat, Siew Chien (Research and Innovation in Technical and Vocational Education and Training, 2022)
This project is aimed to design and develop a 3D animated video application for computer evolution. The development of a 3D animated video application of computer evolution aims to help educators present the topic of computer evolution to students in a simple and more creative method. At the same time, this application can also increase students’ interest and understanding of the topic of computer evolution. A literature review was conducted to further assist in designing products that are suitable for the latest generation. The ADDIE model was used in the development of this product. The ADDIE model has five phases, namely analysis, design, development, implementation, and evaluation. In the analysis phase, the developer makes an analysis of the problems that occur and an analysis of the software and hardware requirements. For the design phase, the developer creates a storyboard that is used as a reference during product development. In the development and implementation phase, the developer develops a product based on a pre-designed storyboard. Products are developed using selected hardware and software. The evaluation and testing process was performed by five experts in the field of creative multimedia from the Faculty of Technical and Vocational Education. Three experts played a role in the evaluation of the product interface design. Meanwhile, two more experts are in the role and content design evaluation of the developed products. The instrument used was an expert checklist form. The collected data were analyzed using frequency and percentage methods. Through the results of the study, all experts gave good and positive feedback on the 3D animation video application of computer evolution developed.